ANALISIS FAKTOR KEPUTUSAN SISWA SMAN 3 BANGKALAN TIDAK MENGIKUTI TES KEMAMPUAN AKADEMIK - Moch. Rizky Septiadi Pradana; Yusrianto Sholeh (STKIP Pesisir Selatan, 2026)
The decline in student participation in the Academic Aptitude Test (TKA) has become a critical issue in the field of education because it relates to students’ readiness to pursue higher education. This study aims to analyze the influence of self-confidence and family support on the decision of 12th-grade students at SMAN 3 Bangkalan not to take the Academic Ability Test (TKA). This study employs a quantitative approach using a survey method by distributing questionnaires to 49 respondents. Data were analyzed using multiple linear regression with the aid of SPSS software. The results indicate that, individually, self-confidence and family support have a positive and significant influence on students’ decisions, with self-confidence being the most dominant factor. Collectively, the two variables account for 76.1% (R² = 0.761) of the variation in students’ decisions. These findings imply the importance of strengthening students’ internal motivation as well as family support in academic decision-making. In conclusion, self-confidence plays a more dominant role than external support in determining students’ decisions, although both remain complementary in shaping readiness to face academic exams and continue their education.